Economic “Short-Termism”: The Debate, The Unresolved Issues, and The Implications for Management Practice and Research - Laverty, Kevin J. (Academy of Management Review, 1996)
In many crucial decisions, the course of action that is moat desirable over the long run is not the best course of action in the short term. This is the dilemma addressed by the ongoing debate over economic “short-termism,” sparked by contentions that U.S. firms are losing to overseas competitors because U.S. management is unwilling or unable to invest in the long run, I argue that the debate has suffered from a limited focus: to address this problem, I present a framework that addresses organizational and individual as well as economic perspectives. I offer a review of concepts, analysis, and evidence, and I suggest a cross-discipline, multilevel research agenda for advancing understanding of this vital topic.